Beta-NMR/ON on-line at the NICOLE facility, ISOLDE - recent magnetic moment studies near double magic Ni-68 - Rikovska, J; Stone, N (2000)
The technique of β-NMR/ON and its use for measurement of nuclear magnetic moments is briefly reviewed. Recent magnetic moment measurements are reported on 67Ni and 67Cu. The relevance of magnetic moments of single-particle (hole) states for study of effects of configuration mixing and mesonic exchange currents is discussed.